Role of historical monuments in the development of tourism sector (Bazian district for example) - Ali, Garmian Hussein; Mohammed, Adnan Ali; Hamad, Pashtiwan Jawad; Al-Saffar, Bahry Salm Fatah (Sulaimani Journal for Humanities, 2026)
Historical tourism is a specialized form of tourism in which tourists visit historical sites. The main purpose of this type of tourism is to learn about events, personalities, civilizations, and past lifestyles They have tourist attractions, such as natural and archaeological resources. Historical monuments in the study area are not only evidence of past events, but also cultural and economic assets that are key components of the tourism development plan. Expert use of this heritage can serve as an effective force for the economic and cultural development of the region. The aim of this research is to show and present the archaeological areas that exist, visited by a large number of tourists and sections, because it has many important and historical monuments, including (Barda Qareman, Bazian Hill, Bazian Castle). It discusses the important events of archaeological and historical tourism, while referring to the concepts and theories related to tourism that have been developed throughout history.
Keywords: Tourism; Archaeological Tourism; Historical Monuments; Bazian; Tourism Development